Advanced characterization of biodiesel from Podocarpous falcatus oil via spectroscopy and DFT-based approaches: Thermal degradation kinetics and stability assessment - Serges Bruno Lemoupi Ngomade; Cyrille Donlifack Atemkeng; Aymard Didier Tamafo Fouegue; Cyrille Ghislain Fotsop; Hilaire Tendongmo; Théophile Kamgaing; Solomon Gabche Anagho; Neeraj Atray (Chemical Thermodynamics and Thermal Analysis)
This study examined the thermal breakdown of Podocarpus falcatus oil (PFO) and its derived biodiesel (BPFO) under dynamic heating conditions. PFO and BPFO were characterized by spectroscopic, computational, and thermo-gravimetric analysis coupled with differential thermo-gravimetric analysis (TGA/DTA). PFO and BPFO's kinetic and thermodynamic properties were examined using Kissinger-Akahira-Sunose (KAS), Flynn-Wall-Ozawa (FWO), and Starink isoconversional kinetic models. The conversion limit was restricted from 0.1 to 0.9 at different heating rates of 5, 7 and 10 °C.min−1. The FWO isoconversional model was properly fitted by the TGA/DTA analytical data, with the highest R2 values of 0.941. Average activation energies were 224.50 kJ.mol−1 for PFO and 108.60 kJ.mol−1 for BPFO. Nonspontaneous and endothermic thermal breakdown was confirmed by positive standard enthalpy (∆H) and standard Gibbs free energy(∆G) values. In contrast, the negative standard entropy (ΔS) indicated a more ordered process. Using density functional theory (DFT) in conjunction with the M05–2X hybrid functional, the computing study was conducted on the two most abundant FAMEs (Fatty acid methyl ester) to achieve the optimum geometry, topology analysis, and electronic properties. There was a good correlation between the computation and experimental results. This study showed that biodiesel's thermal and oxidation stability with regard to time could be accurately predicted using the TGA/DTA approach.